The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1017/bpp.2019.38
|View full text |Cite
|
Sign up to set email alerts
|

Official advice improves mortgage-holders’ perceptions of switching: experimental evidence

Abstract: Encouraging consumers to switch to lower-rate mortgages is important both for the individual consumer's finances and for functioning competitive markets, but switching rates are low. Given the complexity of mortgages, one potential regulatory intervention that may increase switching rates is to provide independent advice on how to select good mortgage products and how to navigate the switching process. Working with a government consumer protection agency, we conducted an experiment with mortgage-holders to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For example, Ashby and Teodorescu (2019) found that reducing the monetary costs of switching between alternatives reduced inertia biases in a binary choice setting. Similarly, reducing the costs of exploration between service providers, e.g., by enforcing transparency of prices and providing easy comparison tools, reduces information costs and tends to alleviate consumer’s inertia biases (e.g., see Timmons et al, 2019 ; Byrne et al, 2020 ; Marandola et al, 2020 ). In fact, encouraging switching between service providers by reducing the associated switching costs is generally understood as a major factor for improving consumer welfare ( BEREC, 2010 ; Ofcom, 2010 ; Marandola et al, 2020 ; Heiss et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ashby and Teodorescu (2019) found that reducing the monetary costs of switching between alternatives reduced inertia biases in a binary choice setting. Similarly, reducing the costs of exploration between service providers, e.g., by enforcing transparency of prices and providing easy comparison tools, reduces information costs and tends to alleviate consumer’s inertia biases (e.g., see Timmons et al, 2019 ; Byrne et al, 2020 ; Marandola et al, 2020 ). In fact, encouraging switching between service providers by reducing the associated switching costs is generally understood as a major factor for improving consumer welfare ( BEREC, 2010 ; Ofcom, 2010 ; Marandola et al, 2020 ; Heiss et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The vignette experiment reported here formed part of a larger study on attitudes to disability policy, with other stages reported in Timmons et al. (2023). The study was hosted online using Gorilla (Anwyl‐Irvine et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The total sample size was determined based on the experimental task that required the most power (a list experiment reported in Timmons et al., 2023). The vignettes experiment was designed such that each version of the vignettes would be shown to at least 250 participants, chosen at random.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many consumers recognise their lack of knowledge and the complexity of the market, citing these as reasons not to engage in switching (Byrne et al, 2020a). The fear that many consumers have of making mistakes ties in with experimental evidence suggesting that consumers who have greater awareness of all that is involved in the mortgage switching process are more willing to switch (Timmons, Barjaková, McElvaney and Lunn, 2022). This is because those who perceive the switching costs more accurately and have a more representative perception of market conditions are also less likely to feel that they would make a mistake in their switching decision.…”
Section: Mortgagesmentioning
confidence: 99%